Problems and Prospects for Development of Family Households in Ukraine - Yavorska, Tetiana; Яворська, Тетяна Іванівна; Яворская, Татьяна Ивановна; Prus, Yurii; Прус, Юрій Олександрович; Прус, Юрий Александрович; Lysak, Oksana; Лисак, Оксана Іванівна; Лысак, Оксана Ивановна; Zavadskykh, Hanna; Завадських, Ганна Миколаївна; Завадских, Анна Николаевна (My University, 2019)
Agriculture in Ukraine is characterized by the most dynamic rates of development among other sectors of the economy in recent years. Its share in the gross product of the country in 2017 amounted to 10.2%, in exports—33.6%. This situation shows that the state is taking real steps to form an effective agricultural policy. There are many different forms of management in agriculture in Ukraine: agricultural enterprises, farms, households. At different stages of the formation of the agrarian market, the pace of development of these forms is unequal.
Keywords: Family Households; Agriculture; Family Farms